Place of cyclosporin A in the therapy of rheumatic diseases - Zemfira Sadullaevna Alekberova; R. G. Goloeva; Zemfira Sadullayevna Alekberova; R G Goloyeva (Современная ревматология)
The paper considers the major effects of cyclosporin A (CsA) in rheumatic diseases (RD). CsA is noted to be effective for a number of RDs and all types of rheumatoid arthritis (RA), including in early RA in adults and juvenile RA; uveitis associated with Behcet's disease (BD) (as the drug of choice); in combination with other disease-modifying drugs; in RD with concomitant viral hepatitis C. The diagnostic criteria for (BD) and the efficacy of CsA for this disease are given according to different authors.